An Interleaved DC/DC Converter with Soft-switching Characteristic and high Step-up Ratio - Yong-Nong Chang (Applied Sciences, 2020)
This study presents a dc/dc converter featuring soft-switching characteristic, high conversion efficiency, and high step-up ratio. The proposed circuit is composed of two parallel-connected boost converters. Only one coupled inductor is used to replace inductors of the boost converters which are interleaved operated at discontinuous-conduction mode (DCM). The current ripples at the input and the output terminals are reduced due to the interleaved operation. By freewheeling the current of the coupled inductor to discharge the stored electric charges in the parasitic capacitors of the active switches, both active switches can fulfill zero-voltage switching on (ZVS). Owing to DCM operation, the freewheeling diodes can fulfill zero-current switching off (ZCS). Therefore, the power conversion efficiency is improved. The operation principle for each operation mode is analyzed in detail and design equations for the component parameters are provided in this report. Finally, a prototype 200 W 48−400 V converter was implemented and measured to demonstrate the effectiveness of the proposed circuit.